Pediatric Radiology On-Call Simulations - Leah Braswell; Carol Thrush; Grace Gephardt; Linda Deloney (Association of American Medical Colleges, 2015)
Abstract Introduction Simulated learning in medical education has been shown to enhance traditional methods of learning. In a safe simulation environment, learners are exposed to real-world situations in order to gain knowledge and experience. This learning opportunity will provide a uniform foundation in the basics of communication and procedural skills while addressing many ACGME Program Requirements for radiology residents. Methods This resource provides instructors with four pediatric radiology clinical scenarios for use in a simulation lab for radiology residents. The purpose of these simulation scenarios is to provide a realistic experience for residents to acquire competency in the diagnosis, management, and communication regarding common pediatric clinical encounters on call. Through these experiences, residents gain comfort with common but challenging clinical scenarios, including intussusception diagnosis, management plan, and parent consent; gastrojejunostomy (GJ) tube dislodgement treatment plan and parent education; hip effusion consultation with emergency department physician and aspiration plan; and contrast reaction simulation with mannequin. This course relies on standardized participants and advanced simulation equipment, as well as faculty or qualified simulation staff to oversee the simulations. Results In 2012, first-year (n = 6) and second-year (n = 6) residents attended the half-day course early in the academic year. As part of an IRB-approved research project, we evaluated the effectiveness of these simulation cases examining data from the residents, who took 18-item pretest and posttest surveys addressing self-perception of mastery. Comparing composite scores for residents' self-ratings on questions 1-10 between pre− and postsimulation training showed statistically significant improvement (p < .001). The median postsimulation score was 3.80, while the median presimulation score was 3.10. Similarly, the median composite score of 4.00 for basic knowledge items (questions 15-18 completed by residents) postsimulation was significantly improved over the presimulation median score of 3.00 (p = .016). The outcomes from the station checklists comparing first− and second-year residents showed the median GJ tube score was 6.00 for second-year residents, a significant difference from the median score of 3.50 for first-year residents (p = .002), indicating progressed skills for more advanced residents. Discussion These results suggest that this introductory simulation workshop is feasible and is an effective method for teaching initial skills in pediatric radiology to first− and second-year residents. To date, the course hasn1t evaluated the durability of knowledge learned. There is no follow-up testing or review of the skills administered at a later date, which is a potential weakness.